Islamic ethics for autism children on iOS - Abd Malik, Sofianiza; Mohamad, Ahmad Fazman Illya; Zainal, Mohd Hafiz; Muhammad Nasir, Nur Dhiyana (2014)
This project involves designing, modelling, rigging and animating 3D Animation Application on Adab (3DAAA) for high functioning autistic students in Akademi Al-Fakih Intelek (AFI). The animation is converted into an application in iOS platform so that it can be viewed through the iOS devices such as iPhone, iPad and iPod. The main objective of this project is to allow high functioning autistic students to learn about adab (manners) through interactive and fun method according to their own pace. This project would help students getting Islamic knowledge and values using the utilised mobile technology in their learning method assist by their parents and teachers.